(untitled) (Research, Society and Development, 2020)
This work aims to problematize the constitution of the Base Nacional Curricular in the area of Natural Sciences by analyzing the way it approaches the specificities of the education of ethnic-racial relations and if it can guarantee possibilities of teaching those topics in the final years of Elementary School. The reason for the development of the research is centered on the fact that, in order to respect the ethnic diversity, a perspective that problematizes structural aspects and takes into account non-ethnocentric cultural practices is necessary. Since BNCC guides the minimum content to which Brazilian students are entitled to learn, it must present elements that corroborate this position. So, at first, we present the process of elaborating this document. Then, we compare the changes present in BNCC over the three versions and look for the presence of terms that explicitly manifest the racial discussion. Finally, through the Discursive Textual Analysis approach, we try to find possibilities implicit in the texts of the learning objectives and skills that indicate paths for the development of ethnic-racial relations discussion. The results point out that there was a change in the approach among the three versions, the second being the one that most points to a perspective of historical, social and cultural contextualization, however none of them explicitly highlights a discussion about the topic. At last, we could find possibilities implicit in the document, when these are confronted with academic productions that detail elements of the contributions of Sciences to the education of ethnic-racial relations.